Flight Information Display System Development Web-Based - Wahab, Immas; Musadek, Ahmad; Ratna Sari, Dewi (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Airport services include widespread dissemination of flight information to passengers. The Flight Information Display System (FIDS) is essential, providing passengers with details like flight data, departure gates, destinations, status, directions, origin, estimated gate arrival time, departure and arrival timings, and flight numbers. The purpose of developing this web-based flight information display system is to facilitate passengers in obtaining flight-related information. This application aims to enhance satisfaction, comfort, and accessibility to flight information. The system utilizes sample flight data input by administrators and accessed by passengers via the internet. The design employs UML and development is executed through a CMS. The research methodology employed is Research and Development (R&D), following the Analysis, Design Development, Implementation, and Evaluation (ADDIE) model